An adaptive thresholding method for segmenting dental X-ray images - Razali M.R.M.; Ahmad N.S.; Bahari M.; Zaki Z.M.; Radman A.; Waidah Ismail (Universiti Teknikal Malaysia Melaka, 2024)
Indexed by SCOPUS